Sprich doch! Department of Education materials for the German Oral examination (Leaving Certificate) - Smyth, Sheila (Gill & Macmillan, 1994)
This book contains material from past examinations for use as practice by students preparing for the Leaving Certificate oral test, with role plays and picture sequences taken from previous German orals. The book includes examiner role-play cards to give students an insight into what is expected of them. Sample vocabulary phrases and follow-on questions are provided with each picture sequence. The book also covers the general question of the oral test by supplying questions on various themes and possible answers.